Creating cultures of thinking the 8 forces we must master to truly transform our schools - Ritchhart, Ron (San Francisco, CA Jossey-Bass, 2015)
"Discover why and how schools must become places where thinking is valued, visible, and actively promoted. As educators, parents, and citizens, we must settle for nothing less than environments that bring out the best in people, take learning to the next level, allow for great discoveries, and propel both the individual and the group forward into a lifetime of learning. This is something all teachers want and all students deserve. In Creating Cultures of Thinking: The 8 Forces We Must Master to Truly Transform Our Schools, Ron Ritchhart, author of Making Thinking Visible, explains how creating a culture of thinking is more important to learning than any particular curriculum and he outlines how any school or teacher can accomplish this by leveraging 8 cultural forces: expectations, language, time, modeling, opportunities, routines, interactions, and environment. With the techniques and rich classroom vignettes throughout this book, Ritchhart shows that creating a culture of thinking is not about just adhering to a particular set of practices or a general expectation that people should be involved in thinking. A culture of thinking produces the feelings, energy, and even joy that can propel learning forward and motivate us to do what at times can be hard and challenging mental work"-- Provided by publisher.
Introduction: Demystifying group and organizational culture -- The purpose and promise of schools -- Expectations: recognizing how our beliefs shape our behavior -- Language: appreciating its subtle yet profound power -- Time: learning to be its master rather than its victim -- Modeling: seeing ourselves through our students' eyes -- Opportunities: crafting the vehicles for learning -- Routines: supporting and scaffolding learning and thinking -- Interactions: forging relationships that empower learners -- Environment: using space to support learning and thinking -- Moving toward transformation -- Appendixes: A. My reflections on the learning activities in this class -- B. Ladder of feedback -- C. Success analysis protocol -- D. Looking at students' thinking (LAST) protocol -- E. Six key principles of the cultures of thinking project -- F. Laying the foundation for a culture of thinking -- G. Leading a culture of thinking at my school -- H. The development of a culture of thinking in my classroom -- I. Assessment ladder.
Includes bibliographical references (pages [329]-350) and indexes.
Keywords: Thought and thinking -- Study and teaching; Critical thinking -- Study and teaching; Cognition in children; Educational change -- United States